Effect of DMSO Solvent Treatments on the Performance of PEDOT:PSS Based Organic Electrochemical Transistors. (4th February 2019) - Lingstedt, Leona V.; Ghittorelli, Matteo; Lu, Hao; Koutsouras, Dimitrios A.; Marszalek, Tomasz; Torricelli, Fabrizio; Crăciun, N. Irina; Gkoupidenis, Paschalis; Blom, Paul W. M.
Abstract: The conductivity of poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonic acid) (PEDOT:PSS) can be strongly enhanced by treatment with high boiling solvents as dimethyl sulfoxide (DMSO). The effect of various DMSO solvent treatment methods on the performance of organic electrochemical transistors (OECTs) based on PEDOT:PSS is studied. The treatments include mixing PEDOT:PSS with DMSO before film deposition, exposing a deposited PEDOT:PSS film to a saturated DMSO vapor, and dipping a PEDOT:PSS film in a DMSO bath. Compared to dry PEDOT:PSS, operating in the OECT configuration causes a significant reduction of its conductivity for all treatments, due to the swelling of PEDOT:PSS by the direct contact of the conductive channel with the electrolyte. The dipping method gives rise to the highest OECT performance, reflected in the highest on/off ratio and transconductance. The improved conductivity and device performance after dipping arise from an enhanced charge carrier mobility due to enhanced structural order. Abstract : The electrical conductivity of PEDOT:PSS can be improved by organic solvent treatments in form of adding a solvent (solvent additive, SA), exposing to a solvent‐vapor (polar solvent vapor annealing, PSVA) or dipping in a solvent‐bath (polar solvent post‐treatment, PSPT) . The enhanced device performance is caused by an increased charge carrier mobility due to an enhanced structural order and domain purification.